Necessary Skills and Personality Traits of Successful Philippine Coast Guard (PCG) K9 Dog Handlers: A Basis for Recruitment and Training Framework - Gemino, Diomedes S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The study involved 33 purposively selected PCG K9 Dog Handlers and aimed to examine the necessary skills and personality traits (O.C.E.A.N.) that contributed to success in their field. It used a mixed-method design, collecting both quantitative and qualitative data concurrently through a validated research instrument. Quantitative data were analyzed using frequency, percentage, ranking, independent t-test, and one-way ANOVA, while qualitative data were examined through coding and thematic analysis. Findings revealed that the top 10 skills commonly demonstrated by successful K9 handlers included: understanding canine behavior; conditioning dogs for basic obedience; emotional and psychological preparedness; skills in demonstrating fundamental dog handling techniques; nonverbal communication (gestures, expressions, body language); teamwork and interpersonal communication; responsible canine handling; physical stamina and agility; situational awareness in canine handling; and trust in the dog’s natural indications. In terms of personality traits, results showed a moderate manifestation of Openness to Experience, high manifestation of Conscientiousness, moderate manifestations of both Extraversion and Agreeableness, and low manifestation of Neuroticism. Additionally, handlers were intrinsically motivated by their emotional attachment to dogs, their skills in managing difficult dogs, knowledge of canine characteristics, trust in dogs’ natural inclination, and a strong sense of purpose in promoting public safety and the welfare of the community. Finally, the study emphasized the need to integrate personality development in training programs. Key recommendations included the adoption of a proposed K9 Dog Handler Recruitment and Training Framework, creation of a K9 Reserve Unit, support for further education, and conducting broader longitudinal studies.